On the Issue of Effective Modeling of The Investment Portfolio of Insurance Companies - BABAYEVA, N.M. (The journal of contemporary issues in business and government, 2021)
The correct formation of the investment portfolio plays an important role in increasing the efficiency of investment activities of insurance companies. The article discusses investment models developed by foreign by scientists in the formation of the investment portfolio of financial organizations, including insurance companies, and issues of their optimization.